Leadership Style and Organizational Effectiveness: Motivation and Engagement as Mediators - Fitria Nur Aisyah; Widya Prananta (Universitas Muhammadiyah Malang, 2026)
This study examines the effect of leadership style on organizational effectiveness and analyzes the mediating roles of employee motivation and employee engagement at PDAM Tirta Moedal Semarang City. Using a quantitative approach, data were collected through closed-ended questionnaires from 100 employees selected by simple random sampling and analyzed using Partial Least Squares Structural Equation Modeling. The main variables were Leadership Style, Employee Motivation, Employee Engagement, and Organizational Effectiveness. The results show that leadership style has a positive and significant effect on employee motivation with β = 0.623 and t = 10.184, employee engagement with β = 0.692 and t = 14.380, and organizational effectiveness with β = 0.361 and t = 3.829. Employee motivation with β = 0.236 and t = 2.975 and employee engagement with β = 0.383 and t = 4.109 also positively and significantly influence organizational effectiveness. The R² value of 0.716 indicates that the model explains 71.6% of the variance in organizational effectiveness. The mediation results confirm that employee motivation and employee engagement significantly mediate the relationship between leadership style and organizational effectiveness, with employee engagement showing a stronger mediating role. Theoretically, this study contributes to organizational behavior and public sector management literature by showing that leadership improves effectiveness through employees’ psychological conditions. Practically, the findings suggest that public service organizations should strengthen supportive, inspirational, and communicative leadership practices to enhance motivation, engagement, productivity, and sustainable organizational effectiveness. These findings emphasize employee centered leadership development to improve service quality and reduce turnover risks in public organizations.